Persentase Kebuntingan Kambing Betina Resipien Setelah Pelaksanaan Embrio Transfer - Ginta Riady; Mulyadi Adam; Idawati Nasution (Jurnal Agripet, 2001)
ABSTRACT. A study on the pregnanncy rate of recipient does following embryio transfer procedure had been carried out. This study used 2 donor does and 10 recipient does. Donor does are subjected to both estrous synchronization (using progesterone in CIDR-G device) and superovulation protocols using follcle stimulating hormone in Folltropin-V. However, recipient does are only subjected for estrous synchronization protocol. Estroussynchronization protocol ni donor does and recepientb ones are conducted at the same tame. Embryo collection is carried out through cervix at day 7 following breeding. Parameter of this study is pregenancy rate of recipient does fillowing embryo transfer. Data collected in this study will be analyzed descriptively. Recipient does received two embryos by non-surgery method. This study showed that recipient does were foun non-pregnant during pregnancy diagnosis. It can be related to the incidence of early embryonic death are nutrion and overcrowding in uterus. It can be conclude that embryo transfer procedure carried out in this study was not effective.